The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/molecules21101329
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of 3-O-Acetyl-11-Keto-βBoswellic Acid (AKBA) and Other Boswellic Acids in Boswellia sacra Flueck (syn. B. carteri Birdw) and Boswellia serrata Roxb

Abstract: Lower percentages of BAs content were obtained when BAs were expressed on the gum resin weight (29% and 16% for B. sacra and B. serrata, respectively). The content of Acetyl-11-Keto-β-Boswellic Acid (AKBA) was higher in B. sacra (70.81 g·kg −1 d. wt; 7%) than in B. serrata (7.35 g·kg −1 d. wt; 0.7%). Our results show that any claim of BAs content in either B. sacra or B. serrata gum resins equal to or higher than 70% or AKBA contents of 30% are simply unrealistic or based on a wrong quantitative determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 29 publications
5
35
0
Order By: Relevance
“…The other components of BS extracts, lacking the keto moiety, were visualized only at a less specific wavelength (210 nm) as already reported [34]. The AKBA concentrations detected in samples A, B, D, and F are similar to those reported by other authors [30, 35], while those found in extracts C and G were 10 or 100 times lower, respectively. It can be hypothesized that extract C belongs to Boswellia species other than B. serrata , due to a wrong botanical identification by local producers.…”
Section: Discussionsupporting
confidence: 88%
“…The other components of BS extracts, lacking the keto moiety, were visualized only at a less specific wavelength (210 nm) as already reported [34]. The AKBA concentrations detected in samples A, B, D, and F are similar to those reported by other authors [30, 35], while those found in extracts C and G were 10 or 100 times lower, respectively. It can be hypothesized that extract C belongs to Boswellia species other than B. serrata , due to a wrong botanical identification by local producers.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, HPLC–DAD coupled with MS is usually used for the qualitative and quantitative determination of pentacyclic triterpenoids . Mannino et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mannino et al. utilized HPLC–DAD–MS to quantitatively determinate the content of boswellic acids in Boswellia sacra Flueck and Boswellia serrata Roxb . Lu et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations